Constructing Virtual Cities by Using Panoramic Images - Ikeuchi, Katsushi; Sakauchi, Masao; Kawasaki, Hiroshi; Sato, Imari (International Journal of Computer Vision, 2004)
Simultaneously acquired omni-directional images contain rays of 360 degree viewing directions. To take advantage of this unique characteristic, we have been developing several methods for constructing virtual cities. In this paper, we first describe a system to generate the appearance of a virtual citys the system, which is based on image-based rendering (IBR) techniques, utilizes the characteristics of omni-directional images to reduce the number of samplings required to construct such IBR images. We then describe a method to add geometric information to the IBR imagess this method is based on the analysis of a sequence of omni-directional images. Then, we describe a method to seamlessly superimpose a new building model onto a previously created virtual city images the method enables us to estimate illumination distributions by using an omni-directional camera. Finally, to demonstrate the methods' effectiveness, we describe how we implemented and applied them to urban scenes.